Новое местонахождение остатков позднеплиоценовых мелких млекопитающих в Николаевской области УССР - Скорик, А.Ф. (Вестник зоологии, 1969)
A new occurrence of the fossil relics of small mammals is described which is located to the east of the Tiligul liman on the beach of the Black Sea near the Southern: outskirts of the khutor «Morskoye» of Tiligul-Berezansky district of the Nikolaev region.
The bone bed is presented here by the bundle of old alluvial sands with partings of gravel, grey and greenish-grey loams containing in abundance the relics of small land vertebrates and fresh water fish.
As a result of studying the specific composition of the fossil small mammals it is established that they, probably, compose the early variant of the Taman faunistic complex. By a number of species the steppe and semi-arid forms prevail and to a less degree — the intrazonal and forest forms. This testifies to the fact that there teas steppe in the territory of the present Ukrainian SSR in the Black Sea area in the second half of the Late Pliocene.